2011
DOI: 10.1007/s11418-011-0538-6
|View full text |Cite
|
Sign up to set email alerts
|

Tinospora cordifolia attenuates oxidative stress and distorted carbohydrate metabolism in experimentally induced type 2 diabetes in rats

Abstract: Diabetes is a chronic metabolic disorder affecting a vast number of people worldwide. Oxidative stress is the causative agent amplifying diabetic complications in various organs by generating noxious amount of free radicals. A huge interest always exists in exploring nutraceuticals from plant materials to replace synthetic drugs in order to overcome their adverse effects and also for economic reasons. The anti-diabetic efficiency of a medicinal plant, Tinospora cordifolia (TC) was studied in experimentally ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 19 publications
2
40
0
Order By: Relevance
“…This may be due to the presence of natural antioxidants in TCE, which help improve the antioxidant status of TCE and CD cotreated rats. Similar results were reported by Sangeetha et al 45 and Agrawal et al 46 in a diabetic rat model.…”
Section: Discussionsupporting
confidence: 90%
“…This may be due to the presence of natural antioxidants in TCE, which help improve the antioxidant status of TCE and CD cotreated rats. Similar results were reported by Sangeetha et al 45 and Agrawal et al 46 in a diabetic rat model.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have also suggested that type II DM can be achieved by administering HFD followed by an injection of STZ to produce insulin resistance and glucose intolerance. 13,10 In addition, significant adiponectin reduction has also been noted to play an important role in the development of insulin resistance and metabolic syndrome. 20,21 The abovementioned induction models have also been reported to exhibit pathological conditions that are similar to those of type II diabetes in humans; however, it has been shown that such attempts have failed to reproduce the complexity of human diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…The stem of Tinospora cordifolia is widely used in the therapy of diabetes by regulating the blood glucose[48] in traditional folk medicine of India. It has been reported to mediate its anti-diabetic potential through mitigating oxidative stress (OS), promoting insulin secretion and also by inhibiting gluconeogenesis and glycogenolysis, thereby regulating blood glucose.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported to mediate its anti-diabetic potential through mitigating oxidative stress (OS), promoting insulin secretion and also by inhibiting gluconeogenesis and glycogenolysis, thereby regulating blood glucose. [48] Alkaloids, tannins, cardiac glycosides, flavonoids, saponins, and steroids as the major phytoconstituents[49] of Tinospora cordifolia have been reported to play an anti-diabetic role.…”
Section: Resultsmentioning
confidence: 99%